(untitled) (KYAMC Journal, 2024)
Non-neural granular cell tumor was first described in 1991 as an unusual primitive, polypoid variant of the conventional GCT (granular cell tumor). To date, this neoplasm remains as a rare entity and the cell of origin is uncertain. While the histological features are similar to the conventional (traditional) GCTs, it represents a distinct entity, as it is negative for S-100 and lacks true nerve sheath differentiation. We report here a case of a 49-year-old male patient with S-100 negative, vimentin positive large benign, ulcerated, bleeding non-neural GCT in the lower rectum. We confirmed the diagnosis histopathologically and immunohistochemically. We treated it by ISRR (Inter-Sphincteric Resection of Rectum) and primary colo-anal anastomosis. We find no other report of non-neural GCT located in the rectum in surgical literature. This is probably the first case of non-neural GCT identified in the rectum. This case report is presented here to document a non-neural GCT located in the rectum for the first time ever reported, and also to highlight the optimum best surgical approach, as we deemed here for this large ulcerated bleeding tumor in the rectum. This rectal non-neural GCT posed here as an unusual differential diagnosis from such more common neoplastic bleeding lesions in the rectum as carcinoma rectum, hemorrhoid, rectal polyp, etc. Here we like to discuss our experience, reviewing in brief the available literature implicating the biological behavior, histopathological and immunohistochemical features, differential diagnosis and therapeutic considerations of neural and non-neural GCTs. KYAMC Journal Volume: 14, No: 03, October 2023: 181-187.